Solar energy in buildings thermal balance for efficient heating and cooling - Chwieduk, Dorota (Elsevier, 2014)
Solar Energy in Buildings presents solar radiation fundamentals and their applications in buildings, supported by theoretical analysis and results of original simulation studies in solar energy availability, collection, and conversion for both active and passive use. In-depth coverage of energy balance and heat transfer in building envelopes is supported by the inclusion of calculations and case studies, while contextualizing within an integrated design approach.--Provided by publisher.